18.1k views
4 votes
Solve the following system of linear equations using the elimination method



Solve the following system of linear equations using the elimination method ​-example-1
User Fravadona
by
4.7k points

1 Answer

4 votes

Answer:

x=-1, y=2, z=3

Explanation:

First at all, you can divide these equations into two group. It is easier to you.

4x-2y+3z=1

3x+y+2z=5

x+3y-4z=-7

3x+y+2z=5

Then, you can simplify these group of equation that you divided.

So, we have to simplify these step by step.

First, we can simplify the first group of equation.

4x-2y+3z=1

3x+y+2z=5

We have to find which variable you want to eliminate. I choose y.

You can multiply the second equation of first group by 2 and eliminate them.

4x-2y+3z=1

6x+2y+4z=10

As the variable of y is same and we can eliminate y by addition.

4x-2y+3z=1

6x+2y+4z=10

become

10x+0+7z=11

10x+7z=11

10x+7z=11 as the third equation.

Next, simplify the second group of equation.

x+3y-4z=-7

3x+y+2z=5

Same way as the previous one. We need to find which variable that you want to eliminate. I choose y.

We need to balance for the first equation x+3y-4z=-7 at least one variable.

We need to multiply this equation by -3 below to get the same value of y to eliminate the above equation.

3x+y+2z=5 (multiply by -3)

-9x-3y-6z=-15

x+3y-4z= -7

-9x-3y-6z= -15

Here we go! Now these group has same value and variable to eliminate.

We can eliminate these equations by addition method.

x+3y-4z= -7

-9x-3y-6z= -15

-8x+0+10z= -22

-8x+10z= -22

Furthermore, we have to combine these equations that we have simplified from the previous groups.

10x+7z=11

-8x+10z= -22

10x+7z=11 and -8x+10z= -22 as a new group.

Finally, it is time to solve these equations!!

10x+7z=11

-8x+10z= -22

First equation of the above group, we can multiply by 10. Like this:

100x+70z=110

Second equation of the above group, we can multiply by 7. Like this:

-56x+70z=-154

So, we can see there are same value from these equation which are +70z and -70z.

Now, we can eliminate this variable by sum these equations.

100x+70z=110

-56x+70z=-154

44x= -44

x= -1

When we get x= -1 , we can use this value to any equation that you want. You can get the same answer as well.

When x= -1,

substitute into 100x+70z=110

100(-1)+70z=110

-100+70z=110

70z=110+100

70z=210

z=3

When z=3 and x= -1, we can substitute into x+3y-4z= -7

-1+3y-4(3)= -7

-1+3y-12= -7

3y=6

y=2

So, the answer is x= -1 , y=2 , z=3

I hope you will understand my solution and explanation. Bye!!

User Prata
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.